Understanding the role of copy number (CNV) in the development of left ventricular hypertrophy in hypertension / Khalid Yusoff and Hoh Boon Peng - Yusoff, Khalid; Hoh, Boon Peng (Research Management Institute (RMI), 2012)
Left ventricular hypertrophy (LVH) is an independent risk factor for the development of heart failure, coronary heart disease and stroke. It develops as a result of hemodynamic overload, for instance, hypertension. Blood pressure is an important determinant of LVH, and a significant proportion of patients with essential hypertension develops this complication. However, this condition varies in a wide range of phenotypes, and studies had shown that patients with LVH may have near-normal blood pressure, suggesting that development of LVH may be due to an independent genetic factor from hypertension. LVH can be reversed with anti-hypertensive (anti-HT) agents. Angiotensinogen receptor blocker like losartan has been shown to improve the reversal effect. However, it is unknown whether using this anti-HT agent alone would be useful in preventing LVH. Hence, identifying HT patients with the risk of LVH may allow this hypothesis to be tested, and if successful, would lead to the prevention, treatment and improvement of prognosis of LVH. We recently carried out a genome-wide scan of copy number variation (CNV) on a group of hyptertensive LVH patients and observed a gain of copy number in AGTRII gene in a group of patients. We attempted to further investigate the role of CNV of this gene in the pathogenesis of LVH. However, we observed no significant contribution of this CNV in the disease complication. Therefore in this study, we attempted to investigate the contributions of rare CNV in the susceptibility of hypertensive LVH, and subsequently to predict the putative molecular pathways in the pathogenesis of LVH.